Morbidity and Mortality of Crystalloids Compared to Colloids in Critically Ill Surgical Patients: A Subgroup Analysis of a Randomized Trial. (December 2018) - Heming, Nicholas; Lamothe, Laure; Jaber, Samir; Trouillet, Jean Louis; Martin, Claude; Chevret, Sylvie; Annane, Djillali
Editor's Perspective: What We Already Know about This Topic: Whether crystalloid or colloids are preferable for treatment of hypovolemic shock in surgical patients remains unclear What This Article Tells Us That Is New: In a preplanned subgroup analysis of a previous trial, the authors compared 28-day mortality in 741 surgical patients with hypovolemic shock who were randomized to crystalloids or colloids Mortality at 30 and 90 days was similar in the two groups, and colloid administration did not increase the need for dialysis Colloid administration did not improve mortality but also did not cause renal injury Background: The multicenter randomized Colloids versus Crystalloids for the Resuscitation of the Critically Ill (CRISTAL) trial was designed to test whether colloids altered mortality compared to crystalloids in the resuscitation of intensive care unit patients with hypovolemic shock. This preplanned analysis tested the same hypothesis in the subgroup of surgical patients. Methods: The CRISTAL trial prospectively defined patients as critically ill surgical patients whenever they underwent emergency or scheduled surgery immediately before or within 24 h of intensive care unit admission and had hypovolemic shock. The primary outcome measure was death by day 28. Secondary outcome measures included death by day 90, the need for renal replacement therapy, or the need for fresh frozen plasma transfusion. Results: There were 741 critically ill surgical patients, 356 and 385 in the crystalloid and colloid arm, respectively. Median (interquartile range) age was 66 (52 to 76) yr, and 484 (65.3%) patients were male. Surgery was unscheduled in 543 (73.3%) cases. Mortality by day 28 did not significantly differ for crystalloids 84 (23.6%) versus colloids 100 (26%; adjusted odds ratio, 0.86; 95% CI, 0.61 to 1.21; P = 0.768). Death by day 90 (111 [31.2%] vs . 122 [31.7%]; adjusted odds ratio, 0.97; 95% CI, 0.70 to 1.33; P = 0.919) did not significantly differ between groups. Renal replacement therapy was required for 42 (11.8%) patients in the crystalloids arm versus 49 (12.7%) in the colloids arm ( P = 0.871). Conclusions: The authors found no survival benefit when comparing crystalloids to colloids in critically ill surgical patients. Abstract : In a preplanned subgroup analysis of a previous trial, the authors compared 28-day mortality in 741 surgical patients with hypovolemic shock who were randomized to crystalloids or colloids. Mortality at 30 and 90 days was similar in the two groups, and colloid administration did not increase the need for dialysis. Colloid administration did not improve mortality but also did not cause renal injury.Supplemental Digital Content is available in the text.